A9.05 Distinct subsets of interferon-stimulated genes are associated with incomplete and established systemic lupus erythematosus. (24th February 2016) - Psarras, A; Md Yusof, MY; El-Sherbiny, YM; Hensor, EM; Wittmann, M; Emery, P; Vital, EM
Abstract : Background and objectives: Type I interferons (IFN-I) are crucial to systemic lupus erythematosus (SLE) pathogenesis. However, IFN-I activity, as measured by interferon-stimulated gene (ISG) expression, has an unclear relationship with clinical features of disease. Incomplete lupus erythematosus (ILE) describes individuals who have new onset of features suggestive of SLE, but do not fulfil diagnostic criteria. Up to 20% of these patients eventually progress to SLE. The objective of this study is to compare ISG expression between patients with ILE and SLE to understand the role of IFN in onset of clinical features of SLE. Materials and methods: Expression of 33 ISGs was measured using qPCR in PBMCs from individuals with SLE (n = 54), ILE (n = 27), and healthy controls (HC; n = 14). SLE was defined using 2012 ACR/SLICC criteria. ILE was defined as ANA +ve, 1–2 clinical ACR/SLICC criteria, and symptom duration <12 months. Factor analysis (FA) was used to reduce expression data to a limited set of factors which were compared between patient groups using ANCOVA test. Results: FA on SLE patients indicated two factors explaining 80% of the data variance. In total, 16 and 14 genes loaded onto Factors F1 and F2 respectively. The majority of variability was explained by F1; however, F2 appeared more relevant to the presence of fully established SLE. F1 and F2 were significantly different between patient groups (p = 0.005 and p = 0.044 respectively). F1 was similarly high in both SLE [SLE:HC=4.22 (1.80, 9.88), p = 0.001] and ILE [ILE:HC=2.96 (1.20, 7.32), p = 0.019]. In contrast, F2 was increased only in SLE [SLE:HC=1.38 (0.95, 2.00), p = 0.086] but not in ILE [ILE:HC=1.02 (0.69, 1.51), p = 0.917]; a significant difference was observed between SLE and ILE patients [SLE:ILE=1.35 (1.04, 1.77), p = 0.026]. Conclusions: IFN-I activity is present in ILE. However, the majority of measured ISG expression (F1) cannot distinguish ILE and SLE. F1 represents genes that distinguish healthy individuals, but show little variation at different stages of the disease development. We define a subset of ISGs (F2) whose expression is only increased in patients with confirmed clinical SLE. ISG expression is not unidimensional: qualitative differences in expression of distinct ISGs contribute to clinical progression after disease initiation.